Analysis of Learning Media for Plant Identification Using Plantamor-Assisted PlantNet on Plantae Materials as a Learning Media Innovation - Tamba, Rhodentia; Indri Andriyatno; Bambang Supriatno; Riandi (IJER (Indonesian Journal of Educational Research), 2024)
Learning media can be used in the learning process to increase student attention, clarify information provided by the teacher, and avoid misconceptions so that the learning process is more interactive, effective, and able to increase student activity in learning. This study aims to analyze various technologies, namely plantNet and plantamor, as innovations in plant identification learning media. This study used a literature study research method with a narrative review design. The results of the analysis show that combining the PlantNet application as a tool for identifying plant species through pictures with the Plantamor website as a tool for validating the identification of plants found because it provides various information about the plants being identified will greatly assist students in learning and facilitate teachers in teaching. Thus, it will create fun for students and teachers.